Evaluation and modeling of structural hysteresis - Takeshi KAWACHI; Yukihisa KURIYAMA; Katsuyuki SUZUKI (Nihon Kikai Gakkai ronbunshu, 2017)
In order to clarify the mechanism of the vehicle body hysteresis affecting “rigidity feeling”, one of the driver's sensory evaluation in the driving test, the influence of friction acting on spot welding flanges on hysteresis, which is drawn by displacement - load diagram under static or relatively slow deformation of double-hat-shaped parts assembled by spot welding, is experimentally evaluated. By measuring the difference between loss energy of a specimen with strong contact on welding flanges and that of another specimen without contact, friction loss (energy dissipation generated only by friction excluding inevitable loss energy for measurement possessed by testing system itself) is calculated. The friction loss rising with increasing load amplitude and load rate confirms that friction hysteresis occurs in the structure even under the elastic deformation. In this paper, the load rate dependence and the extrapolation point to the zero load rate are evaluated as the dynamic and static characteristics of friction loss, respectively. As a result, the dynamic characteristic obtains a result proportional to the load amplitude, and the static characteristic is proportional to the square of the load amplitude. Additionally, a model with the reaction force as the sum of linear elastic resistance due to bending and shear deformation, Coulomb friction proportional to amplitude of displacement and viscous friction is proposed. Using this model, the prediction of static and dynamic characteristic of the friction loss shows good agreement with results of the experiment. Finally, the friction-induced hysteresis led from the model is quantitatively discussed.